Ted Chiang’s Asian American Amusement at Alien Arrival - Esaki, Brett J. (Religions, 2020)
In the 2016 movie Arrival, aliens with advanced technology appear on Earth in spaceships reminiscent of the black obelisk in 2001: A Space Odyssey. The film presents this arrival as a serious problem to be solved, with the future of human life and interplanetary relationships in the balance. The short story, “Story of Your Life” by Ted Chiang, on which the film was based, takes a different, amusing route that essentially depicts an ideal vision of the era of colonialism. To articulate this reading, this article will compare Chiang’s science fiction (SF) to the genre in general and will take Isiah Lavender III’s positionality of otherhood to reveal how Chiang’s work expresses a Chinese American secular faith in a moral universe. It will analyze the narrative form in Chiang’s collection, Stories of Your Life and Others, and will use it to compare the prose and film versions of “Story of Your Life.” It will also explain how Chiang may be using a nonlinear orthography and variational principles of physics to frame multileveled humor. It utilizes theories of humor by John Morreall and analyses of Chinese American secularity by Russell Jeung and concludes that Chiang’s work reflects concerns and trends of Asian Americans’ secularized religions.